THE INFLUENCE OF HEALTH EDUCATION TOWARD THE LEVEL OF KNOWLEDGE AND MOTIVATION IN THE USE OF FAMILY PLANNING PROGRAMS WITH THE LONG-TERM METHOD OF CONTRACEPTION - Pradista Harini; Arum Lusiana; Sri Widatiningsih (Poltekkes Kemenkes Semarang, 2019)
Background: Family planning is an effort to regulate the birth of children, distance, and the ideal age for giving birth, regulating pregnancy, through promotion, protection, and assistance by reproductive rights to create a quality family. Efforts to health education about contraception can increase knowledge that can influence the attitudes and motivations that exist in someone to take action in choosing a contraceptive method. Purpose : The purpose of this study was to determine the effect of health education on the level of knowledge and motivation in the use of MKJP in women of childbearing age. Methods: This research was conducted in Wuwuharjo Village, Kajoran District, Magelang Regency. This study uses One Group Pretest and Postest correlation analysis with a crossectional approach and sampling using the Systematic Random Sampling method. The respondents used were 80 people. Data collection was done by questionnaire instruments and data were analyzed bivariate by testing Marginal Homogeneity and McNemar. Result: The results of the study show that there is an influence between health education on the level of knowledge and motivation in using MKJP in women of childbearing age. This can be seen from the significance value produced 0.1. Conclusion: The recommendation for further research is about the routine of health education by using media that are appropriate to the needs of educational routines that increase the knowledge and motivation of women of reproductive age couples in contraceptive use.